NF1 mutations identify molecular and clinical subtypes of lung adenocarcinomas - Camille Tlemsani; Nicolas Pécuchet; Aurelia Gruber; Ingrid Laurendeau; Claire Danel; Marc Riquet; Françoise Le Pimpec‐Barthes; Elizabeth Fabre; Audrey Mansuet‐Lupo; Diane Damotte; Marco Alifano; Armelle Luscan; et al. (Cancer Medicine, 2019)
Abstract The tumor suppressor gene neurofibromin 1 (NF1) is a major regulator of the RAS‐MAPK pathway. NF1 mutations occur in lung cancer but were not extensively explored. We hypothesized that NF1‐mutated tumors could define a specific population with a distinct clinical and molecular profile. We performed NF1 sequencing using next generation sequencing (NGS) in 154 lung adenocarcinoma surgical specimens with known KRAS, EGFR, TP53, BRAF, HER2, and PIK3CA status, to evaluate the molecular and clinical specificities of NF1‐mutated lung cancers. Clinical data were retrospectively collected, and their associations with molecular profiles assessed. In this series, 24 tumors were NF1 mutated (17.5%) and 11 were NF1 deleted (8%). There was no mutation hotspot. NF1 mutations were rarely associated with other RAS‐MAPK pathway mutations. Most of patients with NF1 alterations were males (74.3%) and smokers (74.3%). Overall survival and disease‐free survival were statistically better in patients with NF1 alterations (N = 34) than in patients with KRAS mutations (N = 30) in univariate analysis. Our results confirm that NF1 is frequently mutated and represents a distinct molecular and clinical subtype of lung adenocarcinoma.